Penyuluhan Kesehatan Gigi Bagi Anak-Anak Di Rptra Sungai Bambutanjung Priok Jakarta Utara - Suraya Suraya; Aprilia Aprilia; Alma Yulana; Annik Setiawati; Aulia Lydia Citra; Lenny Lenny (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2018)
Children in the Sungai Bambu village of Sungai Bambu are very active, cheerful and dynamic. They always play in the Sungai Bambu Integrated Child Friendly Public Space (RPTRA). Unfortunately there are problems experienced by these children, namely lazy bathing and brushing their teeth. The main problem is that in addition to lack of awareness of brushing teeth they also do not understand how to brush teeth properly. For this reason, sental health extension is needed for children and their parents to educate on the importance of brushing your teeth properly. This community service activity was held at RPTRA Sungai Bambu Tanjung Priok North Jakarta on Friday, 29 June 2018. The event was attended by 49 people consisting of children and parents. Communication extension begins with showing videos, an explanation of toothbrushes followed by a demonstration and simulation of the correct way to brush your teeth. In conclusion: Children and parents are enthusiastic about the dental health extension provided and begin to understand how to maintain dental health.